Drafting effect in cycling: On-site aerodynamic investigation by the 'ring of fire' - Spoelstra, A.; Mahalingesh, N.; Sciacchitano, A. (Proceedings, 2020)
An on-site Ring of Fire (RoF) experiment is performed at the Tom Dumoulin bike park in Sittard-Geleen, the Netherlands. The current work investigates the aerodynamic drag of a cyclist following a lead cyclist at different lateral and longitudinal separations; additionally, the athletes` skills to maintain their position and distance with respect to the preceding riders are evaluated. The effect of the relative size of the lead cyclist on the drag area of the drafting cyclist is also investigated. The results show drag reductions of the trailing cyclist in the range from 27% to 66% depending on the longitudinal and lateral separation from the leading rider. The aerodynamic advantage of the drafting rider decreases with increasing lateral and longitudinal separation between riders, with the lateral separation found to be more relevant. Besides this, the drag reduction of the drafting cyclist benefits from an increase in drag area of the leading cyclist.